Additive manufacturing and surface functionalisation of Ti6Al4V components using self-assembled monolayers for biomedical applications - Vaithilingam, Jayasheelan (2015)
The ability to provide mass customised and biocompatible implants is increasingly important to improve the quality of life. Additive manufacturing (AM) techniques have obtained increasing popularity and selective laser melting (SLM), a metal-based AM technique with an ability to build complex and well defined porous structures, has been identified as a route to fabricate customised biomedical implants. Surface modification of an implant with a biomolecule is used to improve its biocompatibility and to reduce post-implant complications. In this thesis, the potential of a novel approach to use self-assembled monolayers to modify SLM fabricated surfaces with therapeutic drugs has been evaluated.